If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(5X + -6) + 3X = 6 + 3X Reorder the terms: -6(-6 + 5X) + 3X = 6 + 3X (-6 * -6 + 5X * -6) + 3X = 6 + 3X (36 + -30X) + 3X = 6 + 3X Combine like terms: -30X + 3X = -27X 36 + -27X = 6 + 3X Solving 36 + -27X = 6 + 3X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3X' to each side of the equation. 36 + -27X + -3X = 6 + 3X + -3X Combine like terms: -27X + -3X = -30X 36 + -30X = 6 + 3X + -3X Combine like terms: 3X + -3X = 0 36 + -30X = 6 + 0 36 + -30X = 6 Add '-36' to each side of the equation. 36 + -36 + -30X = 6 + -36 Combine like terms: 36 + -36 = 0 0 + -30X = 6 + -36 -30X = 6 + -36 Combine like terms: 6 + -36 = -30 -30X = -30 Divide each side by '-30'. X = 1 Simplifying X = 1
| 9x^2-12x+4=6x-4 | | 6c=-29 | | 3(2+v)=6+2(v+1) | | -6+3y=5 | | a/1.5=0.8 | | 11/2x=9/20 | | 3n+4n=42 | | 3=3(k-6) | | -2X^2=25-10X | | 3x-7(x-2)=10 | | 29p-21p+6p-13p=17 | | r/9-1=-4 | | 6q-2q=20 | | (7x+2)+3+8x= | | x*2-4=5 | | 54/63 | | 8n-3n=95 | | -6=x^2+2x | | -2/8=-0.9+y | | -2n+6(-2n+1)=-38-3n | | 84+(5x-9)=(-2+12x) | | -100=-6x+2(7x-10) | | 4x-6(7x-18)=168 | | 7d-d+11d-13d-3d=12 | | m^3/4(m^-1/2+5) | | -8/3n+21=-1/3n | | 0.75-0.50-4=12 | | X+23+14+x= | | 7d-d+11d-13d+3d=12 | | 3(d-8)-5=9(d+2) | | -58=-29n | | x*2-7=3 |